Is There Gender Inequality in Plastic Surgery? Evaluation of Society Leadership and Composition of Editorial Boards. Issue 2 (February 2020) - Chen, Kevin; Ha, Grace; Schultz, Benjamin D.; Zhang, Ben; Smith, Mark L.; Bradley, James P.; Thorne, Charles H.; Kasabian, Armen K.; Pusic, Andrea L.; Tanna, Neil
Abstract : Background: Women now constitute 40.5 percent of integrated plastic surgery residents; however, in 2007, women represented only 11.3 percent of the leadership positions in plastic surgery societies and journal editorial boards. The authors analyzed female representation in these societies and editorial boards over the past 10 years. Methods: Names of board members from the major plastic surgery societies (American Society of Plastic Surgeons, The Plastic Surgery Foundation, and American Society for Aesthetic Plastic Surgery, among others) for the past 10 years and the major plastic journals ( Plastic and Reconstructive Surgery, Annals of Plastic Surgery, and so on) from the past 5 years were extracted from their websites. The yearly percentage of female plastic surgery residents was obtained from Accreditation Council for Graduate Medical Education published data. The proportions of women in society leadership, editorial boards, and residency were compared with data analyses of time series trend and linear and Auto Regressive Integrated Moving Average time series modeling. Results: Over the past 10 years, the percentage of female residents has grown steadily, from 21.84 percent to 37.31 percent. Similarly, female representation in society leadership has grown from 6.78 percent to 20.29 percent. Both growth coefficients were statistically significant and showed no statistical difference between the two. In contrast, editorial board leadership over the past 5 years showed statistically insignificant growth and showed a statistically significant difference when compared to the growth of the percentage of female residents and female representation in society leadership. Conclusion: Female representation in plastic surgery society leadership shows promising growth, whereas their representation on editorial boards showed significantly less growth, which may reflect the slower turnover on these boards.